The efficacy of single pharmacist medication review among type II diabetic patients who take six chronic medications or more: a case-control study - Danielle Harmatz; Shlomo Vinker; Talia Wagner; Tal Raveh; Eugene Merzon; Avivit Golan Cohen (BMC, 2022)
Abstract Background Pharmacist medication review has been implemented in many health organizations throughout the world in an attempt to alleviate the underlying risk of polypharmacy in elderly patients. These consultations are often frequent and prolonged, and are thus associated with increased costs. To date, data regarding the most effective way to utilize pharmacist consultations for the improvement of health status is scant. Aim To evaluate the effectiveness of a single pharmacist consultation on changes in chronic medication regimes and on selected outcomes of diabetes 1-year after the consultation. Methods A case-control study included an intervention group of 740 patients who had pharmacist consultations and a reference group of 1476 matched patients who did not have a pharmacist consultation. 1-year outcome measures were compared including changes in medications, improved safety, and objective variables such as Hba1c, blood pressure, and lipid profile. Results In the pharmacist consultation group, there were significantly more treatment changes ([mean 1.5 vs. 0.7, p < 0.001 medications were stopped], and [mean 1.3 vs. 0.4, p < 0.05 medications were started]). Patient safety improved with a general reduction in opiates and benzodiazepines ([50.0% vs. 31.6%, p < 0.05 opioids were stopped] and [58.8% vs 43.8%, p < 0.001 benzodiazepines were stopped]). Sulfonylurea treatment reduced (10.7% vs. 3.6%, p < 0.05 patients who stopped Sulfonylurea) and Glucagon-like peptide-1 receptor agonists (GLP-1) increased (16.4% vs. 11.2%, p < 0.001 patients who started GLP-1). Additionally, HbA1c levels showed a small decrease in the pharmacist consultation group ([− 0.18 ± 1.11] vs. [− 0.051 ± 0.80], p = 0.0058) but no significant differences were found regarding blood pressure or lipids profile. Conclusion A single pharmacist consultation beneficially impacted specific clinical and patient safety outcomes. Pharmacist consultations may thus help resolve polypharmacy complexities in primary care.